Prognostic value of high-sensitivity troponin I after cardiac surgery according to preoperative renal function. Issue 20 (15th May 2020) - Nam, Karam; Shin, Kyung Won; Kim, Tae Kyong; Kim, Kyung Hwan; Kim, Ki-Bong; Jeon, Yunseok; Cho, Youn Joung
Abstract : Abstract: Cardiac troponin levels can be elevated without myocardial injury in patients with renal impairment. However, the prognostic value of elevated troponin levels after cardiac surgery has not been well evaluated in patients with renal impairment. We evaluated the relationship between postoperative troponin levels and mortality following cardiac surgery according to preoperative renal function. Among 3661 patients underwent cardiac surgery between March 2005 and December 2015, 1909 patients were analyzed after excluding those with insufficient laboratory data, preoperative myocardial infarction, underwent Cox-Maze or redo surgery, or with a follow-up period <30 days. The primary outcome was risk of 30-day mortality according to elevated postoperative high-sensitivity cardiac troponin I (hs-cTnI) levels in varying degrees of renal function. Secondary outcomes included long-term cardiac-cause and all-cause mortality during the median follow-up of 52 months. After adjustment for risk factors, elevated peak postoperative hs-cTnI was associated with 30-day mortality [adjusted odds ratio 1.028, 95% confidence interval (CI) 1.013–1.043, P < .001], long-term cardiac-cause [adjusted hazard ratio (HR) 1.013, 95% CI 1.009–1.017, P  < .001] and all-cause mortality (adjusted HR 1.013, 95% CI 1.009–1.016, P  < .001), in patients with preoperative normal renal function [estimated glomerular filtration rate (eGFR) ≥60 ml/minute/1.73 m 2 ]. However, in patients with renal impairment (eGFR < 60 ml/minute/1.73 m 2 ), hs-cTnI levels were not associated with mortality following cardiac surgery. Elevated hs-cTnI levels following cardiac surgery did not predict short- and long-term mortality in patients with preoperative renal impairment. Abstract : Supplemental Digital Content is available in the text